Tribute to Roger Guillemin, a pioneer in neuroendocrinology (1924–2024), Nobel Prize in Physiology or Medicine - Mougin, Christiane; Rossier, Jean; Bloch, Bertrand (Comptes Rendus Biologies, 2024)
Roger Guillemin discovered and characterized the hypothalamic factors that control anterior pituitary functions. He consequently demonstrated that these brain peptides regulate a large number of major body activities through neuroendocrine mechanisms. This especially include growth, fertility and reproduction, endocrine gland functions and stress. These seminal works paved the way to major applications in many fields of physiology and medicine for diagnosis, pharmacology and therapy, far beyond the initial discovery and properties of these molecules, including in cancerology, immunology, inflammation, drug addiction and behavior.